The School of Hope: A New Category towards the Counternarrative of Competencies - Mosquera Mosquera, Carlos Enrique (2019)
The purpose of this manuscript is to rethink the administration of the school in the midst of dispersion as a place of hope towards the generalized contingency and channeling in which the control society has subjected it, which privileges a story about education in terms of competencies at the service of business and not in terms of knowing how to live with others and build a more humane society.